Improvement of electromagnetic torque of BLDC motor for electrical cutter application - Kahar, Muhammad Izanie; Raja Othman, Raja Nor Firdaus Kashfi; Khamis, Aziah; Karim, Kasrul Abdul; Abdul Shukor, Fairul Azhar; Ab Ghani, Ahmad Fuad; Rejab, Rofizal Mat (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
As the advancement of brushless direct current (BLDC) motor is rising, it has been an advantage to use the motor for a wide range of applications. Its robustness and torque development have benefited small applications, such as the agriculture cutter. However, dropping performances of conventional BLDC are affected by the shape of the rotor that has unused magnetic flux. Therefore, this research aimed to analyze the electromagnetic torque by reducing the unused flux from an electromagnetic point of view. Two BLDC models with different slot-pole numbers and rotor types were modeled and simulated with equal permanent magnet volume, and magnetomotive force (MMF). Finite element method (FEM) software was used to compute back electromotive force (BEMF), cogging torque, electromagnetic torque, and magnetic flux density of the BLDC models. As a result, 9/8 slot-pole with zero ferromagnetic underneath the permanent magnet had the highest BEMF and torque produced compared to the conventional type, with a percentage difference of 27%. In conclusion, this research presents the motor that had an improvement of electromagnetic torque for electrical cutter application.